2016
DOI: 10.3389/fmicb.2016.01782
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Factors Shape Aquatic and Sedimentary Microbial Community Structures in the Lakes of Western China

Abstract: Little is known about the relative importance of spatial and environmental factors to structuring aquatic and sedimentary microbial biogeography in lakes. Here, we investigated the microbial community composition (MCC) of the water (n = 35) and sediment (n = 35) samples from 16 lakes in western China (salinity: freshwater to salt saturation; pairwise geographical distance: 9–2027 km) using high-throughput sequencing and evaluated the relative importance of spatial and environmental factors to microbial (includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 43 publications
5
30
0
Order By: Relevance
“…() found rare bacteria to be to a greater extent randomly assembled and, finally, Yang et al . () found that spatial factors were most important for both. Further, it has been shown that assembly mechanisms can differ between habitat generalists and specialists (Szekely and Langenheder, ; Liao et al ., ; Wu et al ., ).…”
Section: Factors Influencing the Importance Of Different Community Asmentioning
confidence: 95%
See 4 more Smart Citations
“…() found rare bacteria to be to a greater extent randomly assembled and, finally, Yang et al . () found that spatial factors were most important for both. Further, it has been shown that assembly mechanisms can differ between habitat generalists and specialists (Szekely and Langenheder, ; Liao et al ., ; Wu et al ., ).…”
Section: Factors Influencing the Importance Of Different Community Asmentioning
confidence: 95%
“…Although community assembly mechanisms have rarely been directly coupled to traits, several authors have shown that dominant assembly mechanisms differ among bacterial groups (e.g., Barberan and Casamayor, ; Bissett et al ., ; Drakare and Liess, ; Szekely and Langenheder, ; Fujii et al ., ; Liao et al ., ). Moreover, several authors have made comparisons between rare and abundant members of lake communities, which could, for example, vary because of differences in their risk of extinction and likelihood for dispersal (Liu et al ., ; Niño‐Garcia et al ., ; Yang et al ., ; Liao et al ., ). It is, however, hard to draw general conclusions from those studies since widely different results have been obtained, partly perhaps because different definitions of rare and abundant taxa were used: for example, Liao et al .…”
Section: Factors Influencing the Importance Of Different Community Asmentioning
confidence: 99%
See 3 more Smart Citations